Severe upper airway obstruction caused by ulcerative laryngitis. Issue 4 (1st October 2001) - Hatherill, M; Reynolds, L; Waggie, Z; Argent, A
Abstract : AIMS: To present our experience of severe upper airway obstruction caused by ulcerative laryngitis in children. METHODS: Retrospective case note review of 263 children with severe upper airway obstruction and a clinical diagnosis of croup admitted to a paediatric intensive care unit (PICU) over a five year period. RESULTS: A total of 148 children (56%) underwent microlaryngoscopy (Storz 3.0 rigid telescope). Laryngeal ulceration with oedema was documented in 15 of these children (10%), median age 14 months (range 10–36) and median weight 10 kg (range 6–12). Twenty seven of the children who underwent microlaryngoscopy (18%) also had ulcerative gingivostomatitis consistent with herpes simplex virus infection. Ulcerative laryngitis was documented in nine of 27 (33%) children with, and in six of 121 (5%) children without, coexistent ulcerative gingivostomatitis. One of the 15 children did not require airway intervention. Nine children required nasotracheal intubation for a median of 4 days (range 3–11) and median PICU stay of 6 days (range 4–14). Five children required tracheostomy ab initio, with a median PICU stay of 30 days (range 20–36), and duration of tracheostomy in situ for a median of 19 days (range 15–253). All 15 children survived. CONCLUSION: Ulcerative laryngitis is more common in our patient population than the few reports suggest. Early diagnostic microlaryngoscopy is recommended in children with severe croup who follow an atypical course.